2020
DOI: 10.55197/qjssh.v1i5.22
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Thinking in Musically Gifted Practices: A Review

Abstract: Divergent thinking is one of the criteria that needed in digging knowledge. It, furthermore, is identified as an innate element and implanted in every gifted individual’s identity especially those who are musically talented. Divergent thinking is nurtured through giftedness features that existed in a gifted individual, including a unique neurological system. This study is to provide understanding towards the process of divergent thinking that happen in musically gifted minds. This study is to review the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, the necessity to solve new practical problems during the night and the increased rate of REM sleep (i.e., indicative of dreaming) also converged possibly leading to higher creativity ( Coolidge and Wynn, 2006 ; Samson and Nunn, 2015 ). Creativity is positively related to musicality and visual arts ( Ismail et al, 2020 ; Sotiropoulos and Anagnostouli, 2021 ). Evidence for a nocturnal overexcited imagination which corroborates the Nocturnal Evolution of Human Musicality and Performativity Theory ranges from contemporary industrial societies, traditional societies, and prehistory.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the necessity to solve new practical problems during the night and the increased rate of REM sleep (i.e., indicative of dreaming) also converged possibly leading to higher creativity ( Coolidge and Wynn, 2006 ; Samson and Nunn, 2015 ). Creativity is positively related to musicality and visual arts ( Ismail et al, 2020 ; Sotiropoulos and Anagnostouli, 2021 ). Evidence for a nocturnal overexcited imagination which corroborates the Nocturnal Evolution of Human Musicality and Performativity Theory ranges from contemporary industrial societies, traditional societies, and prehistory.…”
Section: Introductionmentioning
confidence: 99%
“…This approach could also be applied in other subjects in order to create an active, fun and enjoyable learning environment as proposed by Ludke (2018). We believe that this approach may enrich music pedagogy and further develope students' Ismail et al, 2020). Therefore, we found that the novelty of this study are movement activities can build students' awareness, improve music skills and strengthen the concept of music for students in line with the philosophy of Dalcroze approach itself.…”
Section: Discussionmentioning
confidence: 75%